A Tractate about the Council of Florence attributed to George Amiroutzes - Gill, Joseph (The journal of ecclesiastical history, 1958)
George Amiroutzes, commonly called the Philosopher for his wide learning, was a native of Trebizond. In 1437 he accompanied John VIII Palaeologus, emperor of Constantinople, to Italy to the Council of Ferrara-Florence as one of the three erudite laymen (the others were George Scholarius and George Gemistus ‘Pletho’) that the emperor took with him to advise him on the difficult theological questions there to be discussed. As the events unfolded division arose in the ranks of the Greeks. First, in Ferrara, there was the question as to what should be the subject of the opening discussion—the addition of the Filioque to the Creed, or the doctrine of the Filioque. Bessarion, metropolitan of Nicaea (later cardinal) and Scholarius (later the patriarch Gennadius) wanted to start with the latter as the more fundamental; Mark Eugenicus, metropolitan of Ephesus, and Gemistus preferred the former and their opinion prevailed. Amiroutzes agreed with Bessarion and Scholarius. In Florence, where the subject of debate was the doctrine of the Filioque, the rift between the two parties was more serious. It was a rift mainly between the leaders, for the majority of the Greek bishops, of a lower intellectual standard, was content to follow. For union the protagonists were Bessarion, Isidore, metropolitan of Kiev and of all Russia, Gregory, the imperial confessor, and Dorotheus, metropolitan of Mitylene. Against union, Mark of Ephesus stood almost alone but indomitable. George Amiroutzes was a staunch supporter of the unionists, who in several of the private conferences of the Greeks bitterly attacked Eugenicus and who gave a written vote in decisive and clear terms in favour of the orthodoxy of the Latin doctrine on the Procession of the Holy Spirit. The decree of union of the Latin and the Greek Churches was promulgated in solemn session on 6 July 1439. It bears the signatures of the emperor, of all the Greek prelates but two (Eugenicus and Isaias of Stauropolis), of five deacons of the Great Church and of several monks. The three ‘philosophers’ did not sign because they were laymen. As is well known, after their return to Constantinople most of the Greek prelates, under the influence of Mark Eugenicus and of popular sentiment, repented of their adherence.